2018
DOI: 10.1159/000493426
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Accurate Identification of <b><i>Candida albicans</i></b> and <b><i>Candida dubliniensis</i></b> by Real-Time PCR and Melting Curve Analysis

Abstract: Objective: Candida albicans and Candida dubliniensis are germ tube-positive pathogenic yeast species. Accurate identification of these two species is warranted since C. albicans is a highly pathogenic species while C. dubliniensis exhibits increased adherence to buccal epithelial cells, reduced susceptibility to azoles and resistance to flucytosine. We have developed a duplex real-time PCR assay for rapid detection and differentiation between clinical C. albicans and C. dubliniensis isolates. Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 35 publications
(54 reference statements)
0
22
1
1
Order By: Relevance
“…Moreover, correct differentiation of this species is especially important for immunosuppressed patients, for example, HIV-infected patients, whose oral cavities are frequently colonized with C. dubliniensis [ 26 , 27 ]. In order to properly identify these species, it is necessary to introduce more advanced diagnostic methods that will standardize the tests using a more unified identification system, e.g., RT PCR [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, correct differentiation of this species is especially important for immunosuppressed patients, for example, HIV-infected patients, whose oral cavities are frequently colonized with C. dubliniensis [ 26 , 27 ]. In order to properly identify these species, it is necessary to introduce more advanced diagnostic methods that will standardize the tests using a more unified identification system, e.g., RT PCR [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Somogyvari et al's study, 25 10 Candida spp were differentiated by analyzing the HRMA of the ITS2 sequence. In a study concluded by Asadzadeh et al, 26 real‐time PCR method based on melting point analysis with SYBR Green dye was introduced as a fast and reliable molecular method to perform accurate diagnosis and differentiation of C albicans and C dubliniensis . Alnuaimi et al 27 identified nine Candida spp using HRMA based on ITS1, 5.8S, and ITS2 sequences, in which they used eight Candida species as positive controls in each run.…”
Section: Discussionmentioning
confidence: 99%
“…and C. albicans genotypes [230]. Furthermore, Asadzadeh et al [231] developed a duplex RT-PCR assay for rapid detection and differentiation between C. albicans and C. dubliniensis by using two species-specific primer pairs and SYBR ® Green dye to differentiate C. albicans and C. dubliniensis isolates via melting curve analysis of RT-PCR amplicons. The amplification products were also analyzed by agarose gel electrophoresis to confirm RT-PCR results.…”
Section: Molecular Methods Used To Detect Yeastsmentioning
confidence: 99%
“…The amplification products were also analyzed by agarose gel electrophoresis to confirm RT-PCR results. Melting temperature (Tm) for reference strains of C. albicans and C. dubliniensis were 86.55 °C and 82.75 °C, respectively [231]. Similarly, quantitative PCR assays to determine the relative Paracoccidioides brasiliensis load in lungs from infected mice were also developed.…”
Section: Molecular Methods Used To Detect Yeastsmentioning
confidence: 99%